ナンキョク チイキサン チイルイ カラ エラレタ カロテノイド - Czeczuga, Bazyli; 井上, 正鉄; イノウエ, マサカネ; Upreti, Dalp Kumar; Inoue, Masakane (1996)
P(論文) 東南極の宗谷海岸, Schirmacher Oasis, 南シェトランド諸島キング・ジョージ島産地衣類33種について, カラム及び薄層クロマトグラフィー法によりカロテノイドを分析した。結果として, α-caroteneをはじめとして21種のカロテノイドの存在を明らかにした。 Column-, and thin-layer chromatography revealed the presence of the following carotenoids in the thalli of 33 lichen species from the Antarctic : α-carotene, β-carotene, δ-carotene, ε-carotene, β-cryptoxanthin, lutein, zeaxanthin, echinenone, hydroxyechinenone, canthaxanthin, α-doradexanthin, β-doradexanthin, astaxanthin, lycopene-5,6-epoxide, lutein epoxide, antheraxanthin, neoxanthin, violaxanthin, auroxanthin, mutatoxanthin, and capsochrome. The total content of carotenoids ranged from 23.25 (Leptogium puberulum) to 123.50μg g^<-1> dry wt (Polycauliona regalis). departmental bulletin paper